MiADMSA abrogates chronic copper-induced hepatic and immunological changes in Sprague Dawley rats. (November 2020) - Patwa, Jayant; Flora, S.J.S.
Abstract: Wilson disease (WD) is an autosomal-recessive disorder associated with the impaired copper metabolism, resulting in hepatic and neurologic manifestations. D-Pencillamine (DPA) is a first-line of treatment however, monoisoamyl 2, 3-dimercaptosuccinic acid (MiADMSA), is gaining recognition recently as a future chelating agent of choice. We evaluated the effects of MiADMSA against copper-induced (20 mg/kg, orally, once, daily for 16 weeks) hepatic and immunological changes in the male Sprague Dawley (SD) rats. Copper overload increased the levels of pro-oxidant and concurrently decreased the levels of antioxidant enzymes in the liver. Increased oxidative stress triggered the up-regulation of pro-inflammatory cytokines (TNF-α, IL-1β, IL-6) in the liver and down-regulated the anti-inflammatory cytokine IL-4. Altered liver function parameters as well as serum immunoglobulins' (IgG, IgA, IgE, and IgM) levels, were also noted. MiADMSA treatment restored most of copper altered biochemical and immunological changes. Further, the histopathological changes proved that MiADMSA treatment ameliorated copper induced hepatic injury. Infra red spectra of liver tissue indicated shift in the characteristic –OH peak during copper exposure while the shifting came to normal in MiADMSA administered rat liver. We conclude that MiADMSA could be a promising antidote for the chronic copper toxicity and possibly in the clinical management of WD. Graphical abstract: Image 1 Highlights: Copper induces hepatic and immunological changes in rats. Copper elicits significant hepatic injury. Increased oxidative stress trigger up-regulation of inflammatory cytokines. Chelation therapy is effect in reducing these changes.